(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Non-Timber Forest Products (NTFPs) contributes to dietary requirement of the households during economic shocks through food and income provisions. This study investigates the contribution of NTFPs to the dietary requirement of households in Kajola Local Government Area of Oyo State, Nigeria. Data from 120 sampled respondents were generated via a simple random sampling technique and interview schedule using a well-structured questionnaire. Descriptive statistics and inferential analytical tool (multiple regression) were used for the analysis. From the results, (60.0%) of the respondents were female. Majority (64.2%) respondents were within their youthful age group of 18-40 years. Also, majority (61.7%) of them were married. Good number (41.6%) of respondents attained secondary education qualification. Majority (38.3%)of the sampled respondents had not more than 5 household size. Equally, (77.5%) of t respondents earned between N20,000- N60,000 monthly from NTFPs sales. Wild fruits (29.2%) and Honey (28.3%) and firewood/charcoal (20.0%) are the most available and exploited NTFPs for dietary requirement by the respondents. Likewise, majority (51.7%) of the respondents sold only NTFPs to contribute to their household’s dietary requirement. explicitly, (89.3%) of the NTFPs harvested were sold by the respondents’ households while only (10.7%) of the NTFPs harvested were consumed. Meanwhile, variable such as respondents age, respondents’ gender, family status, academic level, core occupation and households’ size were all significant at 5% probability level and positively impacted NTFPs contribution to households’ dietary requirement. Hence, the need for strategies and investment in NTFPs value addition for all year round dietary availability to households, and a means...